Análises proteômicas de conídios do fungo patogênico humano Paracoccidioides sp - Moreira, André Luís Elias (2014)
The paracoccidioidomycosis (PCM) is a systemic disease caused by the thermo dimorphic fungus Paracoccidioides spp.. The route of infection of the PCM occurs by the inhalation of conidia or mycelia fragments. Until now, no proteomic studies were performed with conidia of Paracoccidioides sp. In this sense, characterize the proteome of the conidia, may contribute to the detailed knowledge of the proteins expressed during the propagation phase and their potential roles in virulence and pathogenicity, providing possible targets for antifungal strategies. For the conidia production, the mycelia of isolate Pb01 (ATCC MYA-826) were cultured in potato agar medium during 90 days at 18 ºC. After production, the conidias were collected and purified. The proteins were extracted and subjected to tryptic digestion with subsequent identification by NanoUPLC-MSE. We identified a total of 242 proteins of conidia of Paracoccidioides. The in silico analysis were used to characterize the proteins present in Paracoccidioides conidia. Proteins as GAPDH, enolase, triosephosphate isomerase, and some glycoproteins like ECM33 and β-1,3-glucanosyltransferase gel2 were identified during analysis. Some of these have been described as adhesins in Paracoccidioides and in other pathogenic fungi. Were also identified proteins related to signal transduction pathways, such as: Ras GTPase, RhoA GTPase and calmodulin, described in other fungi involved in morphologic changes. Proteins related to evasion, defense and virulence of the fungus, such as HSP90, catalase, mitochondrial peroxiredoxin Prx1, have been described with functions related to temperature shifts or oxidative stress provided by the host environment, were also identified. These results highlight that Paracoccidioides conidia contain proteins that can contribute to its maintenance in the environment and have molecules related to important processes necessary for the initial steps of infection in the host.